Diagenetic controls on fluid flow and mechanical properties in Rotliegend reservoir sandstones - Monsees, Alexander C. (KIT Scientific Publishing, 2021)
Reservoir quality of Rotliegend sandstones is mainly controlled by their permeability, and porosity, and their mechanical properties. Thus, diagenetic porosity-reducing processes need to be understood to evaluate reservoir quality and geotechnical properties in sandstones. Best reservoir qualities are achieved in mature sandstones with large amounts of quartz cementation. The relative length of grain-contacts compared to the respective grain diameter is identified as proxy for rock strength.